The Influence of Tax Understanding, Service Effectiveness, and Sanctions on Vehicle Tax Payment Compliance in Tabanan Regency - Ni Kadek Nia Sintiya Dewi; Ni Made Suci (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Taxes are a crucial source of state revenue supporting economic growth and development, including at the regional level. Motor vehicle taxes, as part of regional taxes, contribute significantly to Regional Original Income (PAD), which is then used to finance various development programs and public services. However, taxpayer compliance remains a challenge for local governments, including in Tabanan Regency. This study examines the influence of tax understanding, service effectiveness, and sanctions on vehicle tax compliance. A quantitative approach was used, using a survey method with 81 respondents recruited through stratified random sampling based on the distribution of taxpayers across ten sub-districts. Data analysis was conducted using multiple linear regression, preceded by validity, reliability, and classical assumption tests. The results indicate that tax understanding and service effectiveness have a positive and significant effect on vehicle tax compliance. Meanwhile, sanctions had no significant effect. Simultaneously, all three variables significantly influenced taxpayer compliance. This finding indicates that efforts to increase compliance should focus on tax education and improving service quality.